Beyond Vaccines: Clinical Status of Prospective COVID-19 Therapeutics - Kumar, Sriram; Çalışkan, Duygu Merve; Janowski, Josua; Faist, Aileen; Conrad, Beate Claudine Gisela; Lange, Julius; Ludwig, Stephan; Brunotte, Linda (Frontiers in Immunology, 2021)
Since November 2019 the SARS-CoV-2 pandemic has caused nearly 200 million infection and caused more than 4 million deaths globally (Updated information from the World Health Organization, as on 2nd Aug 2021). Within only one year into the pandemic, several vaccines were designed and reached approval for the immunization of the world population. The remarkable protective effects of the manufactured vaccines are demonstrated in countries with high vaccination rates, such as Israel and UK. However, limited production capacities, poor distribution infrastructures and political hesitations still hamper the availability of vaccines in many countries. In addition, due to the emergency of SARS-CoV-2 variants with immune escape properties towards the vaccines the global numbers of new infections as well as patients developing severe COVID-19, remains high. New studies reported that about 8% of infected individuals develop long term symptoms with strong personal restrictions on private as well as professional level, which contributes to the long-lasting socioeconomic problems caused by this pandemic. Until today, emergency use-approved treatment options for COVID-19 are limited to the antiviral Remdesivir, a nucleoside analogue targeting the viral polymerase, the glucocorticosteroide Dexamethasone as well as neutralizing antibodies. The therapeutic benefits of these treatments are under ongoing debate and clinical studies assessing the efficiency of these treatments are still underway. To identify new therapeutic treatments for COVID-19 now and in the post-pandemic era, diverse experimental approaches are under scientific evaluation in companies and scientific research teams all over the world. To accelerate clinical translation of promising candidates, repurposing approaches of known approved drugs are specifically fostered but also novel technologies are being developed and are under investigation. This review summarizes the recent developments from the lab bench as well as the clinical status of emerging therapeutic candidates and discusses possible therapeutic entry points for the treatment strategies with regard to the biology of SARS-CoV-2 and the clinical course of COVID-19.